Optimizing Financial Management to Improve the Financial Performance of the West Papua Provincial Government - Kaleb Yohan Karubaba; Ansar Ansar; Gunawan Gunawan; Kurniawsaty Kurniawsaty; Mattalatta Mattalatta (International Journal Labs, 2026)
This study aims to analyze the optimization of financial management to improve the financial performance of the West Papua Provincial Government by examining the influence of human resource competency, accountability, and organizational commitment, with supervision quality as a mediating variable. The research employed a quantitative approach with a sample of 212 employees from five Regional Apparatus Organizations, selected using proportional stratified random sampling. Data were collected through a questionnaire and analyzed using Structural Equation Modeling (SEM) with AMOS software. The results show that human resource competency, accountability, and organizational commitment have a positive and significant effect on supervision quality. Furthermore, these three variables also directly and positively influence regional financial management performance in a statistically significant manner. Supervision quality was also found to have a positive and significant effect on financial management performance. In addition, supervision quality partially mediates the relationship between each independent variable and regional financial management performance. These findings confirm that improving human resource competency, accountability, and organizational commitment, supported by strong supervision quality, can enhance regional financial management performance. The study implies that local governments should invest in capacity building, enforce accountability mechanisms, and strengthen internal supervision systems